TANAH ULAYAT DAN KEMISKINAN PEREMPUAN - Silvia Hanani (Universitas Islam Negeri Imam Bonjol Padang, 2013)
The community family land tenure in the traditional Minangkabau fall entirely on women (Bundo Kanduang). Communal land should not be dominated by men and should not be traded individually. If community family land has been converted from women, then women will lose a valuable asset in his people even poverty will colonize Minangkabau women. As a result women will be trapped at the Minangkabau starvation issues, domestic violence, prostitution, and dropout from school or college. Keywords : Minangkabau, matrilineal, communal landCopyright © 2013 by Kafa`ah All right reservedDOI : 10.15548/jk.v3i1.67